Analysis of intercomponent energy transfer in the interaction of oscillating-grid turbulence with an impermeable boundary - McCorquodale, Mark W.; Munro, R.J. (American Institute of Physics, 2018)
New experimental results are presented that investigate the nature of the intercomponent energy transfer that occurs in the interaction between oscillating-grid turbulence and a solid impermeable boundary, using instantaneous velocity measurements obtained from two-dimensional particle imaging velocimetry (PIV). Estimates of the pressure-strain correlation term (Πsij) of the transport equation of the Reynolds stress tensor, which represents intercomponent energy transfer, are obtained using the PIV data from a balance of the remaining terms of the transport equation. The influence of Πsij on the flow is examined by computing the energy spectra and conditional turbulent statistics associated with events in which intercomponent energy transfer is thought to be concentrated. Data reported here are in support of viscous and “return-to-isotropy” mechanisms governing the intercomponent energy transfer previously proposed, respectively, by Perot and Moin [J. Fluid Mech. 295, 199–227 (1995)] and Walker et al. [J. Fluid Mech. 320, 19–51 (1996)]. However, the data reported also indicate the presence of a weak net intercomponent energy transfer from the boundary-normal velocity components to the boundary-tangential velocity components over a thin region outside the viscous sublayer which is not captured within existing models of intercomponent energy transfer at the boundary.